Analisis Peran Pelatih dalam Pengembangan Mental Atlet Bulu Tangkis pada Galaxy Club Medan - Ahady, Muhammad Yan; Kinanti, Richa Putri; Sukmana, Dian Takher; Rahma, Fanisa (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the role of coaches in the mental development of badminton athletes at Galaxy Club Medan. The research method used is a qualitative approach, which involves interviews with 30 athletes and coaches, direct observation during training sessions, and documentation. The findings indicate that coaches play a significant role in motivating athletes, providing psychological support, and implementing strategies to enhance discipline and mental resilience. Furthermore, there was a noticeable improvement in athletes' confidence and performance after participating in the training program. The conclusion of this study emphasizes that coaches not only serve as technique instructors but also as mentors who support the mental development of athletes, which is key to success in badminton competitions.